MENINGKATKAN HASIL BELAJAR SISWA DALAM KETERAMPILAN MENYIMAK MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI MADRASAH IBTIDAIYAH - Tutus Rani Arifa; Barsihanor Barsihanor; Sari Kumala; Jumiati Jumiati (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
The purpose of this research is to anallyse the effort of improving correct reading student ability in Grade IV at MI Miftahul Jannah Sungai Tabuk Kalimantan Selatan in Bahasa Indonesia subject through of contextual teaching and learning approach. The research executed in MI Miftahul Jannah Sungai Tabuk Kalimantan Selatan which have location at Sungai Tabuk Street Banjar Kabupaten Banjar Kalimantan Selatan.The research method used is class action research by using cycle model of Stephen Kemmis and Mc. Taggart with four phases in every cycle, that is planning phase, action execution, observation and reflection. Result of the research proving that data obtained from study process in improving correct reading student ability through of contextual teaching and learning approach in this research is efficacy. At cycle I, correct reading student ability reached 67,70, and then, at cycle II correct reading student ability mount to become 83,51. Thereby, study by using contextual teaching and learning approach can improve correct reading student ability. Implication of the research is show that contextual teaching and learning approach can be one way to increase the correct reading student ability at Bahasa Indonesia subject in IV MI Miftahul Jannah Sungai Tabuk Kalimantan Selatan